Religiosidade e Qualidade de Vida dos Pacientes com Insuficiência Renal Crônica em Hemodiálise - Nepomuceno, Fabio Correia Lima (2011)
This research aimed to study the religiosity and quality of life (QV) of 100 patients with chronic renal failure on hemodialysis treatment, with the range of age varying from 18 years old to 90 years old, being 50 man and 50 women. After the ethical procedures, there were applied the following questionnaires: Socio-Demographic Data, WHOQOL-bref and Religious Attitude Scale. For statistical analysis the data were entered in the SPSS platform, executing calculations of percentages, analyzing Cronbach's alpha, used on the Student T test, Pearson correlation calculations, variance analysis, in addition to the average and standard deviations to describe the profile of participants. During the entire process of data collection it was used a field journal to write informal notes about the content of the patients speeches, presented on tables with the positive and negative interpretations of their speeches, using the analysi of Bardin and Lexical. The results found enabled the identification of the time of the chronic kidney disease with the minimum period of 12 months and maximum period of 300 months of disease, ranging from 1 month to 144 months of treatment. Regarding the religious options, 60% of the sample described themselves as catholic. With respect to minimum load factor considered for interpretation of components, it was found that on the range of religious attitudes, the first component gathered 8 items, with saturation ranging between 0.83 and 0.48, had a standard deviation of 8,6 and a variance of 74.6%, with Cronbach's alpha of 0.87. The second component grouped 6 items, with saturation varying from 0.80 to 0.55, standard deviation of 7.7 and a variance of 59.1%, Cronbach's alpha 0.86. The third component collected 7 items, ranging from 0.70 to 0.47, standard deviation was 5.8 and variance 34.1%, alpha of Cronbach's was 0.86. It was observed on the research that the self-assessment about QV averaged 3.8 with a standard deviation of 0.8. On satisfaction with their health, we obtained an average of 3.2 with a standard deviation of 1. The Physical Domain averaged 9.6 with a standard deviation of 2.5. On the Psychological Field it was found an average of 22 with a standard deviation of 4. On the Field Level of Independence there was an average of 12 with a standard deviation of 3. On the Social Relations Domain it was averaged 11 with a standard deviation of 2.5. Finally, the Environmental Domain, where it reached an average of 29 with a deviation of 4.5. That component 1 of the Religious Attitude Scale was correlated with the psychological domain of WHOQOL-bref (r = 0.21, p <0.05). Moreover, there is also a positive correlation between this component and the social relationships domain (r = 0.25, p <0.05). You can also verify a positive correlation between the component 2 of the religious attitude with the independence level of QV (r = 0.28, p <0.01) and the domain of social relationships (r = 0.22, p <0.05). Finally, it is possible to observe a positive correlation between the component 3 of the Religious Attitude Scale with the level of independence domain (r = 0.22, p <0.05), with the social relationships domain (r = 0.22, p <0.05) and the environmental domain (r = 0.23, p <0.05). There was also a positive correlation between satisfaction with the QV and the religious component 2 (r = 0.22, p <0.05). Regarding the duration of the disease and treatment time with the domains of QV, there was a negative correlation between duration of disease and physical domain (r = -0.20, p <0.05), a negative correlation between duration of illness and level of independence domain (r = -0.24, p <0.05) and a negative correlation with strong statistical significance between disease duration and social relationships domain (r = -0.27, p <0.01). It was found on this research that there is an influence of religion with the QV of patients with chronic renal failure, which means, it was observed that the components of the religious attitude had a positive correlation with social relationships, psychological, level of independence and the environment. However, there was no influence of religiosity with the physical domain. Thus, it was observed that religion is a source of comfort and hope to patients, empowering them and promoting general welfare, helping with the acceptance of this inevitable condition.